Lenin i elektrofikatsiya - Shass, Yulii; Kobelev, Vasilii (КУБУЧ (Kubuch), 1932)
Constructivist poster with photo montage of Lenin and electrical infrastructure and illustrations of lightbulbs and electrical towers 1969 reproduction of 1935 poster art. Original title: Ленин и электрофикация PO-1014